Seeds of change: native and non-native assemblages of dryland riverine seedbanks - Jaiden Johnston-Bates; Fran Sheldon; Jane A. Catford; Samantha J. Capon (Regional Environmental Change, 2026)
Seedbanks are a reservoir of plant diversity from which plants can regenerate. Seedbanks are particularly important in dynamic, disturbance-prone landscapes characterised by environmental variation. Understanding the composition of seedbanks and their role in standing vegetation dynamics provides insights into past and future vegetation change, including the potential for plant invasions under different scenarios. In disturbed ecosystems, seedbank composition is often overlooked as a critical component of invasion dynamics. Here, we investigate the composition of soil and litter seedbanks across riverine habitats (instream, riparian and floodplain) in the heavily modified agricultural landscapes of the northern Murray–Darling Basin, eastern Australia. Using germination trials, we examined spatial variation in native and non-native seedbank assemblages and explored likely environmental drivers of seedbank composition as well as similarity to the standing vegetation. Germinable seedbanks comprised 42 native and 34 non-native species. Native seedbanks were more abundant, species rich and functionally diverse, while non-native seedbanks were largely dominated by annual forbs and grasses. Non-native seedbank composition, particularly where the abundance and richness of germinable seeds was high, was associated with agricultural land use transformation and hydrological variation, reflecting the roles of disturbance, stochasticity and opportunism in invasion dynamics. Floodplain seedbanks harboured over 20% more non-native species than either riparian or instream habitats. Many native and non-native species were unique to either the seedbank (33 species) or standing vegetation (51 species), demonstrating the differences between these assemblages at the time of surveys. Current management does not adequately consider seedbank composition, overlooking its contribution to both native regeneration and invasion potential.

Ecology of freshwater mussels, ecosystem engineers: a global review with focus on Hyriidae - Michelle J. Hobbs; Songyan Yu; Mark J. Kennard; Fran Sheldon (Biodiversity and Conservation, 2026)
Freshwater mussels (Order Unionoida) are widespread across intermittent to perennial waterbodies on every continent except Antarctica. Their aquatic ecosystem roles span filtration, nutrient cycling, linking food webs, and habitat provision. They alter energy exchange between water column and sediments and enhance benthic productivity, which has led to them being described as ‘ecosystem engineers.’ They are also a significant food and cultural resource to many communities globally. Freshwater mussels are threatened by climate change and anthropogenic alteration of aquatic ecosystems, undergoing drastic population declines and at least 21 species extinctions. It remains uncertain how the decline of this important invertebrate filter feeder may affect aquatic ecosystems. We conducted a broad examination of the literature using a text mining and topic modelling approach to identify key research themes within freshwater mussel ecology, knowledge gaps and areas of taxonomic and geographical bias. Our current understanding of freshwater mussels as ecosystem engineers draws heavily from studies on taxa from North America and Europe, namely Unionidae and Margaritiferidae. However, our case study on Hyriidae, which inhabit Australasia and South America, found compelling evidence that Hyriid mussels also function as ecosystem engineers. They are powerful filter feeders, modulate water quality, alter planktonic and benthic community composition and productivity, and add physical structure to habitats. They exhibit remarkable flexibility in diet and habitat, leaving many questions on ecological roles in different contexts. Managing aquatic systems to benefit freshwater mussels would be an important step to safeguard populations and associated ecosystem benefits, particularly in Australia and other regions where mussels have infrequently been considered.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Site reduction in redundant ecosystem sampling schemes - Spencer Hays; Bandana Kumari; Ben Stewart-Koster; Edward L. Boone; Fran Sheldon (Environmental and Ecological Statistics, 2021)

Effects of light and nutrients on periphyton and the fatty acid composition and somatic growth of invertebrate grazers in subtropical streams - Fen Guo; Martin J. Kainz; Fran Sheldon; Stuart E. Bunn (Oecologia, 2016)

Using diatom indices for water quality assessment in a subtropical river, China - Xiang Tan; Fran Sheldon; Stuart E. Bunn; Quanfa Zhang (Environmental Science and Pollution Research, 2013)

Terrestrial invertebrates of dry river beds are not simply subsets of riparian assemblages - Alisha L. Steward; Jonathan C. Marshall; Fran Sheldon; Bronwyn Harch; Satish Choy; Stuart E. Bunn; Klement Tockner (Aquatic Sciences, 2011)

Functions of riparian forest in urban catchments: a case study from sub-tropical Brisbane, Australia - Michael J. Newham; Christine S. Fellows; Fran Sheldon (Urban Ecosystems, 2011)

Incorporating Natural Variability into the Assessment of Ecological Health in Australian Dryland Rivers - Fran Sheldon (Hydrobiologia, 2005)

Cryptic species and morphological plasticity in long‐lived bivalves (Unionoida: Hyriidae) from inland Australia - Andrew M. Baker; Chris Bartlett; Stuart E. Bunn; Katrina Goudkamp; Fran Sheldon; Jane M. Hughes (Molecular Ecology, 2003)
Molecular (mitochondrial DNA, isozyme) and morphological diversity of freshwater mussels (Family Hyriidae) was examined at 21 sites encompassing four large river systems, across southwest Queensland, Australia. Evidence was found for two major morphological groups. One group, which occurred in every river system, closely matched a recognized species ( Velesunio ambiguus ) both morphologically and in a well‐supported lineage within a mitochondrial phylogeny generated from partial cytochrome c oxidase subunit I (COI) sequences. The second group most closely matched Velesunio wilsonii in shell morphology but formed three deeply divergent mitochondrial DNA lineages. All four lineages occurred sympatrically in some areas and displayed corresponding fixed differences at nuclear allozyme loci, which suggests an absence of recent hybridization and the presence of separate species.

River Red Gum (Eucalyptus camaldulensis Dehnh.) organic matter as a carbon source in the lower Darling River, Australia - Cathy Francis; Fran Sheldon (Hydrobiologia, 2002)

Changes in biofilms induced by flow regulation could explain extinctions of aquatic snails in the lower River Murray, Australia - Fran Sheldon; Keith F. Walker (Hydrobiologia, 1997)